2004
DOI: 10.1007/s10350-004-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Management of Prolapse of the Ileoanal Pouch

Abstract: Although the incidence of pouch prolapse is relatively low in this survey, the number of cases reported far exceeds the previous known experience. The possibility of this clinical entity should be considered in the differential diagnosis of ileoanal pouch dysfunction. Such recognition should lead to correction of prolapse and pouch salvage in the great majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 10 publications
(10 reference statements)
1
32
0
2
Order By: Relevance
“…In 2003, Ehsan et al 7 , reported on 83 patients with pouch prolapse. These data were based on a survey of all North American members and fellows of The American…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2003, Ehsan et al 7 , reported on 83 patients with pouch prolapse. These data were based on a survey of all North American members and fellows of The American…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6] Ileal pouch prolapse is a rarely reported complication. One previous study, 7 reported the condition in 83 patients in a survey of colorectal surgeons in North America. While there was a 94% success rate reported with surgical repair, there were no data on long-term follow-up with associated recurrences.…”
Section: Introductionmentioning
confidence: 98%
“…The main inconvenience is that right colic arcade preservation is time-consuming and might potentially lead to more ileal pouch intussusception or prolapse, otherwise already described after IPAA [31,32]. Another drawback is an increased risk of pouch ischemia [14,31].…”
Section: Optimizing Mesenteric Lengtheningmentioning
confidence: 99%
“…The pathogenesis is unknown, but there has been a theoretical consideration about the tension of pouch mesenterium. Patients presents with a sensation of incomplete evacuation, seepage, Surgical treatment was performed in 52 patients through transanal, transabdominal or combined approach, with a success rate of 94 % [4]. A single-centre study reports similar numbers, with an overall incidence of 0.3 % (11 out of 3,176 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the experience with management of the complication is very limited. The surgical treatments reported include transanal repair, transabdominal pouchopexy and transabdominal revision or removal [3,4]. A single case-report describes a successful robotic-assisted laparoscopic pouchopexy [5].…”
Section: Introductionmentioning
confidence: 99%